The effectiveness of the transactional analysis on mental well-being and empathy in nurses - Rounak Khalili-Tajareh; Hamzeh Ahmadian (Chronic Diseases Journal)
BACKGROUND: A healthy interpersonal relationship is a key contributor to nurses' success in their occupation. Hence, nurses equipped with essential interpersonal skills know how to treat patients with dignity and respect, and perform their jobs more effectively. Despite the rapidly growing body of research on various aspects of transactional analysis (TA), only a few studies have addressed the role of TA in the nursing area. This paper reports on a study that investigates the effectiveness of TA on mental well-being and empathy among nurses in Sanandaj, a city in the west of Iran.